Disputes and conflicts within construction contracts in the Icelandic construction industry - Birkir Kúld Pétursson 1984- (2015)
The construction industry suffers from frequent disputes and conflicts between all parties of construction contracts. No public data is in place to estimate the general cost of disputes within the sector. A new regulation has recently taken effect and among the updated amendments is the requirement for contractors to obtain a quality management system. Disputes and conflicts are to be recorded in these quality management systems. In this thesis, structured interviews were conducted with participants from construction contractor firms in Iceland. The main goal of the study was to determine the degree of compliance towards the mandatory quality management system outlined in clause 112 of the building code from 2012, determine the type and frequency of conflicts origin and acceptance in the project lifecycle and determine the room for improvements in terms of reducing cost divided from disputes and conflicts. This thesis explores the literature and summarizes the main definitions of disputes and conflicts. The thesis also explores disputes caused by building failures. The study applies different types of disputes, conflicts and building failures found in the literature, to the project life cycle. The frequency of each type of conflict, dispute and building failure is explored and the impact estimated. The compliance towards the requirements of the new building regulation in Iceland was tested. The main findings indicate that compliance towards the requirements of quality management systems of the building regulation at the time of the research was low. The findings also indicate that disputes, conflicts and building failures are identified at the final stage of the project life cycle. The frequency of each type of conflict, dispute and building failure reveals that most factors are very similar in impact although some rank higher than others. The results suggest there is a low industry wide use of ÍST30 in construction contracts. The findings indicate there is a clear room for improvements.